ANALISA DAN PENGUJIAN SISTEM ANTENA PENERIMA POWER BEAM M5 DALAM KOMUNIKASI WIRELESS BERBASIS FIBER OPTIC - ., Reinaldo Parulian Simanjuntak (Jurnal Teknik Elektro Universitas Tanjungpura, 2016)
Needs of the community, especially people in big cities on the internet today as if he had become such a part of daily routine, one of which is to use the facilities Hotspot, which refers to certain places that provide Internet service with WLAN technology (Wireless Local Area Network). Hotspot emitting device commonly referred to as the Access Point. There are various types of devices from different vendors Access Point IT companies. Ubiquiti Networks is a communications technology company. One of its products is NanoStatioM52 (NSM5) and Power Beam M5. NanoStation device is an integrated antenna type used is a directional antenna with a coverage of 60 Â° while the Power Beam with 15 Â° coverage, then the direction of the signal beam pattern tends to be directed and can not reach clients that are far behind the device. In building a local communication system here uses two (2) pieces of antennas as the transmitter and receiver to be installed facing so that the receiving antenna can capture signals emitted by the transmitting antenna. Installation of these devices is done in two (2) different locations namely the transmitting antenna installed in the Great Komp.Bali Agung III and receiver antennas mounted in New Jl.Karya Baru II. Tests conducted at a radius between the transmitter and receiver antenna only, with the received signal strength parameters to perform pingtest to determine the speed of the download or upload or download and upload speeds, also to test the feasibility of the application speedtest.net and speedof.me on both sides of the transmitter and receiver. From the test results, the mounting location between the transmitter and receiver are working with a good performance and are in a radius of 690 meters with an attenuation value of 104.45 dB path loss. In addition to testing and analysis of the installed devices is also conducted tests in the shooting of a CCTV using a laptop where CCTV is also included in the system in the wake of the communication device. Key words: Kata kunci : Access Point, NanoStation M5, Power Beam M5, CCTV